An Analysis on the Undergraduate Students’ Citing Habit in Thesis Writing - Elvira Labosang; S Syamsia (Jurnal Langua, 2022)
This study aims to investigate the students’ habit in writing citation in their thesis. As a scientific paper, a thesis should be formatted according to the style allowed or accepted by the institution. By involving 83 thesis written by undergraduate students on an English program of a college in North Maluku, this descriptive qualitative study revealed that most students used APA style as required by the college. Moreover, the students made many mistakes in writing citation ranged from non-italicized book title to non-recorded quotation. Data from interview revealed that the students made these mistakes due to some factors that we assumed the causes of the students’ citing habit. Overall, plagiarism has been noted as the main factor responsible for those mistakes.